2016
DOI: 10.1152/ajpendo.00159.2016
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of the Sertoli cell androgen receptor disrupts male fertility

Abstract: Recently, we created a unique gain-of-function mouse model with Sertoli cell-specific transgenic androgen receptor expression (TgSCAR) showing that SCAR activity controls the synchronized postnatal development of somatic Sertoli and Leydig cells and meiotic-postmeiotic germ cells. Moderate TgSCAR (TgSCARm) expression reduced testis size but had no effect on male fertility. Here, we reveal that higher TgSCAR expression (TgSCARH) causes male infertility. Higher SCAR activity, shown by upregulated AR-dependent tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In gain‐of‐function mouse model with Sertoli cell‐specific transgenic AR, Hazra et al . () demonstrated altered Leydig cell function, markedly reduced Sertoli cell numbers, increased germ cell apoptosis, and, consequently, reduced sperm output, and disrupted fertility. These findings suggest that conditions linked to significantly upregulated AR in Sertoli cells may lead to spermatogenic impairment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In gain‐of‐function mouse model with Sertoli cell‐specific transgenic AR, Hazra et al . () demonstrated altered Leydig cell function, markedly reduced Sertoli cell numbers, increased germ cell apoptosis, and, consequently, reduced sperm output, and disrupted fertility. These findings suggest that conditions linked to significantly upregulated AR in Sertoli cells may lead to spermatogenic impairment.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that elevated expression of the AR in Sertoli cell of adult male adversely affected testis physiology. In gain-of-function mouse model with Sertoli cell-specific transgenic AR, Hazra et al (2016) demonstrated altered Leydig cell function, markedly reduced Sertoli cell Figure 8 Effects of Notch pathway inhibition on testosterone-regulated claudin-5 and claudin-11 mRNA and protein expression. (A) Cells were treated with a vehicle (control, C), 10 nM testosterone (T), 50 lM DAPT, or 50 lM DAPT + 10 nM T for 24 h. (B) Cells were treated with transfection reagent (TR) alone (control, C), TR + non-targeting siRNA (negative control, NT), 50 nM RBP-J siRNA, TR + 50 nM RBP-J siRNA.…”
Section: Discussionmentioning
confidence: 99%
“…34 These findings point to possible mechanisms related to local androgen supersensitivity following inhibition of DHT by finasteride. In transgenic mice, upregulated androgen receptor expression specific to sertoli cells induced infertility, 35 suggesting that normal DHT levels after finasteride treatment with increased androgen receptor may underlie impaired spermatogenesis.…”
Section: Proposed Pathophysiological Mechanisms Contributing To Sexua...mentioning
confidence: 99%
“…When the AR transgene was injected into a prenatal mouse model, precocious maturation of SCs occurred and limited the window for SC proliferation. The production of fewer SCs can lead to lower-than-normal sperm output ( 74 ).…”
Section: Androgen Receptor Signaling Pathway In Sertoli Cells Can Reg...mentioning
confidence: 99%